2004
DOI: 10.1128/aac.48.6.2244-2250.2004
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequences of Six Penicillin-Binding Protein Genes from 40 Streptococcus pneumoniae Clinical Isolates Collected in Japan

Abstract: All six penicillin-binding protein (PBP) genes, namely, pbp1a, pbp1b, pbp2a, pbp2b, pbp2x, and pbp3, of 40 Streptococcus pneumoniae clinical isolates, including penicillin-resistant S. pneumoniae isolates collected in Japan, were completely sequenced. The MICs of penicillin for these strains varied between 0.015 and 8 g/ml. In PBP 2X, the Thr550Ala mutation close to the KSG motif was observed in only 1 of 40 strains, whereas the Met339Phe mutation in the STMK motif was observed in six strains. These six strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
47
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 28 publications
4
47
2
Order By: Relevance
“…Due to this variation it is difficult to distinguish PBP mutations involved in resistance development from alterations present due to the distinct origin of the gene. Comparison of a large number of sequences from resistant clinical isolates revealed that at least one of two sites is changed in most resistant PBP2x isolates, both of which are located in the active site cavity of the enzyme: Q552E close to the K547TG triad and T338A(P,G) within the S337TMK motif (3,7,14,43,44,47,54,57). Curiously, most of the many PBP2x mutations identified in spontaneous cefotaxime-resistant laboratory mutants are distinct from changes seen in clinical isolates, including the T338 mutation (32), suggesting that other selective forces are acting outside the laboratory.…”
mentioning
confidence: 99%
“…Due to this variation it is difficult to distinguish PBP mutations involved in resistance development from alterations present due to the distinct origin of the gene. Comparison of a large number of sequences from resistant clinical isolates revealed that at least one of two sites is changed in most resistant PBP2x isolates, both of which are located in the active site cavity of the enzyme: Q552E close to the K547TG triad and T338A(P,G) within the S337TMK motif (3,7,14,43,44,47,54,57). Curiously, most of the many PBP2x mutations identified in spontaneous cefotaxime-resistant laboratory mutants are distinct from changes seen in clinical isolates, including the T338 mutation (32), suggesting that other selective forces are acting outside the laboratory.…”
mentioning
confidence: 99%
“…The resistance pbp1a primers were designed to target four amino acid substitutions (Thr5743Asn, Ser-5753Thr, Gln-5763Gly, and Phe-5773Thr) that are common to all penicillin G (PCG)-intermediate and -resistant isolates (29). The resistance pbp2x primers were designed to target amino acid substitutions in the 337STMK motif, and the resistance pbp2b primers were designed to target amino acid substitutions close to the 448SSN motif (25,28). The primers for amplification of the ermB (224-bp) and mefA (294-bp) genes were gleaned from a published sequence (21).…”
mentioning
confidence: 99%
“…The RESIST group showed 96% sequence identity with two strains registered in PubMed, SP00080 and SP00081 (31). When amino acid sequences were compared, the RESIST group strains showed 99% identity to SP00080, 98% identity to SP00081, and 99% identity to unregistered strains J1 and J88 (4).…”
mentioning
confidence: 94%
“…2) (13). The RESIST group strains showed 100% sequence identity in this resistant region to the PRSP SP00091, S. oralis 5296, and Streptococcus mitis B6 strains and 99% sequence identity to Streptococcus sanguis 1907 and PRSP DN87/577 (Table 2) (11,13,31). The pbp2b gene in the RESIST group strains contained a second resistant block that was not associated with PRSP probe 2.…”
mentioning
confidence: 99%